Pemberdayaan Komunitas Remaja Dropout Sekolah Melalui Gerakan Sadar Literasi Islam Moderat Dalam Menangkal Paham Radikal Di Desa Tenggulun Solokuro Lamongan - Alimul Muniroh; Arif Mansyuri (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2018)
This assistance was carried out in the village of Tenggulun Solokuro Lamongan which was the origin of the Bali bombing bombers I. Although the movement was not visible, the remnants of the jihadist ideology certainly could not just disappear from Tenggulun village. This assistance aims to strengthen literacy regarding moderate Islam in dropout youth from Tenggulun village so that they are fully aware of the importance of peaceful religious knowledge and also an affirmation of the teachings of moderation of Islam as a religion which is rahmatan lil ‘alamin. From the mentoring process, the results show that moderate Islamic thinking is very useful for teens who want to learn peaceful Islam, while according to adolescents dropping out to study moderate Islam is tantamount to studying Islam that is rahmatan lil ‘alamin.